RecA-like domain 2 of DNA-dependent ATPase A domain, a SWI2/SNF2 protein, mediates conformational integrity and ATP hydrolysis. Issue 3 (27th June 2018) - Bansal, Ritu; Arya, Vijendra; Sethy, Ramesh; Rakesh, Radhakrishnan; Muthuswami, Rohini
Abstract : ATP-dependent chromatin remodeling proteins use the energy released from ATP hydrolysis to reposition nucleosomes in DNA-dependent processes. These proteins are classified as SF2 helicases. SMARCAL1, a member of this protein family, is known to modulate both DNA repair and transcription by specifically recognizing DNA molecules possessing double-strand to single-strand transition regions. Mutations in this gene cause a rare autosomal recessive disorder known as Schimke Immuno-Osseous Dysplasia (SIOD). Structural studies have shown that the ATP-dependent chromatin remodeling proteins possess two RecA-like domains termed as RecA-like domain 1 and RecA-like domain 2. Using Active DNA-dependent ATPase A domain (ADAAD), the bovine homolog of SMARCAL1, as a model system we had previously shown that the RecA-like domain 1 containing helicase motifs Q, I, Ia, II, and III are sufficient for ligand binding; however, the Rec A-like domain 2 containing motifs IV, V, and VI are needed for ATP hydrolysis. In the present study, we have focused on the motifs present in the RecA-like domain 2. Our studies demonstrate that the presence of an aromatic residue in motif IV is needed for interaction with DNA in the presence of ATP. We also show that the motif V is required for the catalytic efficiency of the protein and motif VI is needed for interaction with DNA in the presence of ATP. Finally, we show that the SIOD-associated mutation, R820H, present in motif VI results in loss of ATPase activity, and therefore, reduced response to DNA damage.